Physicochemical properties and effects of fruit pulps from the amazon biome on physiological parameters in rats - Rosan Fortunato Seixas, Fernanda [UNESP]; Kempfer Bassoli, Bruna; Borghi Virgolin, Lara [UNESP]; Chancare Garcia, Laís; Soares Janzantti, Natália [UNESP] (MDPI, 2021)
This study aimed to analyze the physicochemical characteristics and the effects of Ama-zonian pulp fruits consumption, such as araçá-boi (Eugenia stipitata), abiu grande (Pouteria caim-ito), araticum (Annona crassiflora), biri-biri (Averrhoa bilimbi L.), and yellow mangosteen (Garcinia xanthochymus), on hematologic, metabolic, renal, and hepatic function parameters in Wistar rats (n = 10 rats/group). The pulp of abiu had the highest levels of soluble solids, sugars, and pH. Biri-biri pulp had the highest levels of ascorbic acid and total titratable acidity, and a low pH. The araticum pulp had higher (p ≤ 0.05) ash content, total phenolic compounds, and antioxidant activity than the pulp of other analyzed fruits. No significant increase in hematocrit, nor reduction of blood glucose, plasma cholesterol, and serum levels of glutamic-pyruvic transaminase (TGP), creatinine, and urea was observed in experimental groups relative to the control group of rats after the consumption of fruits pulp. The intake of abiu and araticum pulps promoted a significant reduction (p ≤ 0.05) in total leukocytes of the experimental groups as compared to the control group and only the intake of araticum significantly increased (p ≤ 0.05) triglyceride blood levels in rats (99.50 mg/dL). The regular consumption of biri-biri pulp for 30 days significantly (p ≤ 0.05) increased serum glutamic-oxaloacetic transaminase (TGO) levels in rats (116.83 U/L) compared to the control group (98.00 U/L). More researches are needed to generate knowledge about these promising Amazonian fruits, supporting the native fruit production, in addition to promoting health in the population and sustainability in the Amazon region.
Keywords: Amazonian fruits; Composition; Metabolic effects